Motion Control of Ultrasound Probe based on Master-Slave Robotic System for Medical Ultrasound Applications - Nazieh Hasan, Ahmed S.Ali, Nazzal Salem, Mohammed A. Hussein (International Journal of Advanced Science and Technology, 2019)
Ultrasound is often used in medicine. The quality of the ultrasound image often depends on the ability of the radiologist. Many researchers have proposed robotic systems to help obtain ultrasound images. In this article, a brief description of ultrasound imaging with the help of a robot is presented. An automated system with a parallel mechanism of 3 degrees of freedom for ultrasound images was developed. This parallel mechanism allows for rotation, yaw and pitch of an ultrasound transducer. The experimental results confirm the good performance of the mechanical system with position tracking. A prototype robotic system ultrasound imaging was tested by gelatin home model. The movement accuracy between master and slave was promising results with good image quality.